Investigation of Students’ Difficulties in Mathematical Language : Problem-Solving in Mathematical Word Problems at Elementary Schools - Agusfianuddin, Agusfianuddin; Herman, Tatang; Turmudi, Turmudi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research investigates students’ mathematical language difficulties in solving word problems in elementary school. This research method uses a descriptive with a qualitative approach. The research subjects were 52 fifth-grade elementary school students using a purposive sampling technique with students of different abilities, namely upper, middle and lower abilities. Data collection techniques included triangulation data sources through tests, interviews, and questionnaires, as well as data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Research findings show that students with upper and middle ability problem solving are in the "low" category, and students with lower ability are in the "very low" category. Students’ difficulties in mathematical language are most dominant in sentence indicators. The dominant error is that students do not write down what they know and ask. The influencing factors are internal factors: students are not used to reading long questions, so word problems are more difficult than telling stories directly; not careful; difficulty connecting to concepts (creating models); and students focus on mathematical symbols, not the language of the problem. External factors: Students are rarely introduced to word problems; the teacher does not use a special approach to word problems material learning; the language in the word problems is not yet communicative and authentic (based on real events, there are actors, settings and themes that are liked); and the environment is less supportive. This research concludes that mathematics word problems have a language structure from informal to formal (symbols) arranged in words, phrases, sentences and discourse. Word problems must be designed with communicative and more authentic language, more continuous learning of word problems is provided in each learning topic, and the learning environment at school and home must be mutually supportive.